Ambiguity and legal compliance - Barnum, Timothy C. (Criminology & public policy, 2021)
This study examines the independent and joint effect of ambiguity and perceived certainty of apprehension on law-breaking decision-making. Data come from a survey of experienced drivers (N = 1147) who viewed videos depicting a car speeding on an interstate highway under experimentally manipulated circumstances. The sampled drivers were generally ambiguity averse, opting to reduce speeding as ambiguity about the perceived certainty of apprehension increased. However, perceived ambiguity interacted with perceived certainty such that increases in ambiguity increased the deterrent effect of ambiguity for low certainty probabilities and decreased the effect for high probabilities.